PENGELOLAAN KESELAMATAN DAN KESEHATAN KERJA (K3) (STUDI PERBANDINGAN PADA DINAS KEBERSIHAN DAN PERTAMANAN DENGAN DINAS PEMADAM KEBAKARAN) PADA PEMERINTAH KOTA PEKANBARU TAHUN 2011-2013 - Mutia, Elsha Dwi; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Immaculacy and Landscaping Official of Pekanbaru City is unity viewing direction, comprehesion and implimitation of development hygiene sector, landscape gardening, greening, street lighting, and decorative lighting having vision that realize Pekanbaru City is cleanest, greening, beautiful and sparkling in Indonesia. Fire Brigade Official Pekanbaru City is govenrmental organizations having main task and fuction that is aid the Pekanbaru’s Mayor for implementing regional authority in prevention sector and fire prevention. Health and Safety Working is one of labor protection aspects for can improve the labor’s quality in Immaculacy and Landscaping Official with Fire Brigade Official Pekanbaru City.The purpose of this research is to know how the management of health and safety working in Immaculacy and Landscaping Official with Fire Brigade Official Pekanbaru City in 2011-2013 and to know any efforts conducted the increase health and safety working that the work accident can be minimized. The study uses descriptive qualitative research methods that describe and interpret the data. Informant in this research are 7 people where researchers already understand the preliminary information about research object and informant research.The result of this study that management of health and safety working in comparison between Immaculacy and Landscaping Official with Fire Brigade Official Pekanbaru City have advantages and disadvantages on Planning, Organizing, Directing, and Controling of Healthy and Safety Working, where the planning in management of healthy and safety working on Immaculacy and Landscaping Official better than Fire Brigade Official. On organizing of health and safety working in both official is equlity having good organizing, whereas on directing and controlling of health and safety working, Fire Brigade Official gives better results than Immaculacy and Landscaping Official. Efforts were made in minimazing work accidents by Immaculacy and Landscaping Official with Fire Brigade Official Pekanbaru City is good enough, it’s more give warning and direction and then provide personal protective equipments to workers in the areas and in the Fire Brigade Official training is becoming more routine.